Notes on Glossadelphus M. Fleisch. (Hypnaceae, Bryophyta) in China - Yi, Zhao-Qin; Mu, Li-Qiang; Jia, Yu (Phytotaxa, 2022)
The genus Glossadelphus has been replaced by Phyllodon. However, Glossadelphus and Phyllodon are still used simultaneously in moss checklist of China. Total of 19 taxa of China published as members of the genus Glossadelphus are examined in this study. Our analyses show that only one species of Phyllodon (P. lingulatus) is recognized in China; twelve taxa of Glossadelphus in China are transferred to other genera (Bryocrumia, Ectropothecium, Entodon, Taxiphyllum); five taxa are excluded from the flora of China, and one species remains uncertain. Among them, two new combinations are proposed, Ectropothecium anomalum comb. nov. and E. falcatulum comb. nov. Myurella brevicosta is newly reduced to a synonym of Bryocrumia vivicolor. Glossadelphus isopterygioides is verified as a synonym of Entodon obtusatus. We newly designate lectotypes for G. anomalus and G. falcatulus. A list of 19 taxa of Glossadelphus of China is provided with their present status.